Central venous thrombosis misdiagnosed as eclampsia in an emergency department. Issue 1 (21st December 2007) - Savage, H; Harrison, M
Abstract : Central venous sinus thrombosis can present in the emergency department with a diverse range of symptoms and signs, including a non-neurological scenario, and it thus poses a diagnostic challenge. It is amenable to treatment, so a patient history and awareness of the condition prompts early diagnosis and instigation of treatment which may reduce morbidity and mortality.